Lean Production Supply Chain and QFD-Analysis in the Process of Healthcare - Nikolaeva, Alena (International Journal of Supply Chain Management, 2018)
The research examines the process of providing medical care to patients, including patients with self-referrals (patients without referral), in the planning and diagnostic department and the trauma department of the city clinical hospital. The aim of the research is to determine the percentage of refusals of "self-converters", patients of the hospital who refused to be hospitalized after the initial examination and laboratory tests, reduce the cost of medical care, increase efficiency, consider options for reducing the percentage of refusals from hospitalization, patients in need of medical care. The result of the research expands the boundaries of the application of the Lean Production Supply Chain philosophy to the service sector. Improvement of the production and pre-production domain of medical services provision through the introduction of lean manufacturing and QFD-analysis, reduction of losses and analysis of the decrease in the number of refusals from hospitalization of "self-converters". The results of the research can be applied in internal and external processes of medical establishments and in organizations engaged in providing services to industrial enterprises. The use of lean manufacturing tools allows reducing all types of losses and servicing cycle time. The application of QFD improves the service process in a full life cycle, not only in the manufacturing field, but also in the service sector.